Raw ceramic slurry, preparation method thereof, zirconium oxide composite aluminum oxide raw ceramic and preparation method of zirconium oxide composite aluminum oxide raw ceramic
By modifying the coupling agent and balancing the zirconia powder, the problem of difficulty in dispersing zirconia powder is solved, the high strength and good dispersion effect of zirconia composite alumina raw ceramics are achieved, and the preparation performance of multi-layer ceramic substrates is improved.
Patent Information
- Application Number
- CN202411432026.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-10-14
AI Technical Summary
In the prior art, there are few researches on the dispersion of zirconia powders and the multi-layer zirconia composite alumina ceramic substrates, resulting in increased production difficulty and poor material performance.
By modifying the zirconia powder with coupling agent and combining the ball milling and drying steps, the organic affinity and lubricity of the zirconia powder are improved to ensure uniform mixing and dispersion of zirconia and alumina powder.
The flexural strength of zirconia composite alumina raw porcelain is improved, ensuring that the average flexural strength after stack sintering reaches ≥600MPa, and improving the overall performance of the material.
Smart Images

Figure CN119707456A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-temperature co-fired ceramics, and in particular to a raw ceramic slurry and a preparation method thereof, and a zirconium oxide composite alumina raw ceramic and a preparation method thereof. Background Art
[0002] Zirconia ceramics have the advantages of high strength, high temperature resistance, and good chemical stability. They are widely used in electronics, machinery, chemical industry, aerospace and other fields. However, zirconia ceramics are usually prepared using nano-zirconia, which has disadvantages such as difficulty in powder dispersion, which greatly increases the difficulty of preparing zirconia ceramics. Alumina ceramics have the advantages of high temperature resistance, wear resistance, electrical insulation, low loss, good chemical stability, and abundant raw material sources. It is one of the most widely used ceramic packaging materials in the electronics industry. Alumina ceramics are widely used in aerospace, power devices, sensors and other fields. However, it still has disadvantages such as low strength and poor fracture toughness, which restricts the development of alumina ceramics.
[0003] Zirconia composite alumina ceramics are ceramic products obtained by doping alumina powder with an appropriate amount (8wt%-15wt%) of zirconia powder and sintering them together. The presence of an appropriate amount of zirconia can retain the original advantages of alumina ceramics while improving their strength. The main mechanism is stress-induced phase transformation toughening and microcrack toughening. At present, the research on zirconia composite alumina ceramics is mostly focused on the preparation of mixed powders of alumina and zirconia and single-layer zirconia composite alumina ceramic plates, the latter of which is mostly used in DBC / AMB copper-clad laminates, while the research and application of multi-layer zirconia composite alumina ceramic materials are relatively rare.
[0004] The preparation of multilayer ceramic materials mostly adopts the tape casting method, in which the powder is evenly mixed with solvents, binders, dispersants, plasticizers, etc., and the slurry is tape cast into green porcelain, and then the multilayer ceramic substrate is obtained by stacking and sintering. Zirconia composite alumina ceramics are prepared using nano alumina powder and zirconium oxide powder. Nano powders usually have the disadvantages of easy agglomeration and difficult dispersion due to their large surface energy. Therefore, whether the powder is fully dispersed in the slurry and whether the two powders are evenly mixed is the key to ensure the high strength of zirconia composite alumina ceramics.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] In order to solve the problems of difficulty in dispersing zirconia powder and lack of research on multi-layer zirconia composite alumina ceramic substrates in the prior art, the present invention provides a raw porcelain slurry and a preparation method thereof, and a zirconia composite alumina raw porcelain and a preparation method thereof.
[0007] Based on this, the present invention has the following technical solutions: In a first aspect, the present invention provides a method for preparing a green porcelain slurry, comprising: S1: mixing a first dispersant, a coupling agent, zirconium oxide powder and a first organic solvent, and obtaining modified zirconium oxide powder after ball milling and drying; S2: mixing the modified zirconium oxide powder, aluminum oxide powder, a second dispersant and a second organic solvent, and preparing a first slurry by ball milling; S3: mixing the first slurry with the binder solution and continuing ball milling, adding a plasticizer after the ball milling and continuing ball milling to obtain the green porcelain slurry.
[0008] The present invention uses a coupling agent to modify zirconium oxide powder, and obtains modified zirconium oxide powder by ball milling and drying. This step can improve the organic affinity and lubricity of zirconium oxide powder, which helps to disperse it in the slurry. Then, the solvent, dispersant, alumina powder and modified zirconium oxide powder are ball milled to obtain modified zirconium oxide powder composite alumina powder. This step can ensure that the alumina powder is fully dispersed and the modified zirconium oxide and alumina are mixed evenly. At the same time, no binder is added in this step to prevent the binder and dispersant from affecting the dispersion effect of the powder due to different dispersion mechanisms. The binder is dissolved in advance, and the binder solution is mixed with the modified zirconium oxide powder composite alumina powder and ball milled again, which can ensure that the powder and the binder are fully mixed and effectively prevent the presence of undissolved binder particles in the slurry.
[0009] Preferably, the coupling agent includes an aluminate coupling agent and / or a titanate coupling agent; more preferably, the added amount of the coupling agent is 1 wt% to 3 wt% of the mass of the zirconium oxide powder.
[0010] Preferably, the first dispersant and the second dispersant are each independently, identically or differently, one or more of EW20000, BYK22552, LD1140 and LD1132-50; more preferably, the first dispersant and the second dispersant are each independently, identically or differently, BYK22552 and / or LD1132-50; Further preferably, the added amount of the first dispersant is 0.5wt%~2.5wt% of the mass of the zirconium oxide powder; the added amount of the second dispersant is 0.5wt%~2.5wt% of the total mass of the modified zirconium oxide powder and the alumina powder.
[0011] Preferably, the zirconium oxide powder is nano monoclinic zirconium oxide powder, and D50 is 400-600 nm; and / or, the alumina powder is nano alumina powder, and D50 is 400-600 nm.
[0012] More preferably, the mass of the modified zirconium oxide powder is 8wt% to 15wt% of the mass of the aluminum oxide powder.
[0013] Preferably, a first ball milling medium is added during mixing in S1, and a second ball milling medium is added during mixing in S2; wherein the particle size of the first ball milling medium is 1-5 mm, and the particle size of the second ball milling medium is 10-15 mm.
[0014] In the present invention, the first ball milling medium is used to disperse the powder better during ball milling, and the second ball milling medium is used to mix the slurry.
[0015] Preferably, the binder solution comprises a binder and an organic solvent, the binder comprises one of PVB and / or PMMA, and the organic solvent comprises one or more of acetone, butanone, ethyl acetate and butyl acetate; more preferably, the addition amount of the binder is 8wt%~12wt% of the total mass of the modified zirconium oxide powder and the alumina powder.
[0016] Preferably, the plasticizer is one or more of dibutyl phthalate and dioctyl phthalate.
[0017] In a second aspect, the present invention provides a green porcelain slurry, which is prepared by the above-mentioned green porcelain slurry preparation method.
[0018] In a third aspect, the present invention provides a method for preparing zirconium oxide composite alumina raw porcelain, comprising: standing the raw porcelain slurry for degassing, and then casting to obtain zirconium oxide composite alumina raw porcelain, wherein the casting speed is 0.4-0.5 m / min.
[0019] The present invention finds that the green porcelain prepared by the method has good apparent quality and the average flexural strength after stacking and sintering is ≥600MPa.
[0020] In a fourth aspect, the present invention provides a zirconium oxide composite alumina green porcelain, which is prepared by the preparation method of the zirconium oxide composite alumina green porcelain.
[0021] The green porcelain slurry and preparation method thereof, zirconium oxide composite alumina green porcelain and preparation method thereof provided by the present invention can improve mixing uniformity and dispersion effect of powder and slurry, thereby improving the flexural strength of green porcelain, by modifying zirconium oxide powder and optimizing the mixing steps. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1This is a SEM image of the zirconium oxide composite alumina green ceramic of Example 1 provided by the present invention. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Unless otherwise specified, the various raw materials used in the examples and comparative examples are commercially available conventional raw materials, and the technical means used are conventional means well known to those skilled in the art.
[0026] Example 1
[0027] This embodiment provides a green porcelain slurry, and the preparation method thereof comprises the following steps: ① Weigh 400g of 3mm zirconia balls, 500g of 5mm zirconia balls, 100g of aluminate coupling agent-modified nano-zirconia powder, 20g of BYK22552, 100g each of anhydrous ethanol and butanone, and place them in a 2L ball mill. Adjust the roller mill speed to 70r / min and mill for 24h. ② Weigh 3000g of 10mm zirconia column, 1000g of 15mm zirconia column, 265g of anhydrous ethanol and butanone, and 120g of PVB and place them in a 5L ball mill. Adjust the roller mill speed to 70r / min and ball mill for 24h; ③ After the ball milling is completed, the slurry in the above 2L ball mill jar is filtered through an 80-mesh screen into the above 5L ball mill jar, and 900g of nano-alumina powder is added to continue ball milling for 7h; ④ After the ball milling is completed, the ball mill jar is removed and 72 g of DBP is added. The speed of the roller mill is adjusted to 30 r / min and the ball milling is continued for 17 h to obtain the green porcelain slurry.
[0028] This embodiment further provides a zirconium oxide composite alumina green ceramic, and the preparation method thereof comprises the following steps: ⑤ After the ball milling is completed, the raw porcelain slurry is filtered out and allowed to stand for 15 minutes, followed by a 20-minute degassing treatment; ⑥ The above slurry was cast into green porcelain at a speed of 0.4 m / min, and then cut, laminated, hot pressed, and cut into strip samples with a length of 40 mm, a width of 6 mm, and a thickness of 5 mm. After sintering, the flexural strength test was performed. The sample number was recorded as T1.
[0029] Example 2
[0030] This embodiment provides a green porcelain slurry, and the preparation method thereof comprises the following steps: ① Weigh 400g of 3mm zirconia balls, 500g of 5mm zirconia balls, 100g of aluminate coupling agent-modified nano-zirconia powder, 20g of LD1132-50, 100g of anhydrous ethanol and 100g of butanone, and place them in a 2L ball mill. Adjust the roller mill speed to 70r / min and mill for 24h. ② Weigh 3000g of 10mm zirconia column, 1000g of 15mm zirconia column, 265g of anhydrous ethanol and butanone, and 120g of PVB and place them in a 5L ball mill. Adjust the roller mill speed to 70r / min and ball mill for 24h; ③ After the ball milling is completed, the slurry in the above 2L ball mill jar is filtered through an 80-mesh screen into the above 5L ball mill jar, and 900g of nano-alumina powder is added to continue ball milling for 7h; ④ After the ball milling is completed, the ball mill jar is removed and 72 g of DBP is added. The speed of the roller mill is adjusted to 30 r / min and the ball milling is continued for 17 h to obtain the green porcelain slurry.
[0031] This embodiment further provides a zirconium oxide composite alumina green ceramic, and the preparation method thereof comprises the following steps: ⑤ After the ball milling is completed, the slurry is filtered out and allowed to stand for 15 minutes, followed by a 20-minute degassing treatment; ⑥ The above slurry was cast into green porcelain at a speed of 0.4 m / min, and then cut, laminated, hot pressed, and cut into strip samples with a length of 40 mm, a width of 6 mm, and a thickness of 5 mm. After sintering, the flexural strength test was performed. The sample number was recorded as T2.
[0032] Example 3
[0033] This embodiment provides a green porcelain slurry, and the preparation method thereof comprises the following steps: ① Weigh 400g of 3mm zirconia balls, 500g of 5mm zirconia balls, 100g of aluminate coupling agent-modified nano-zirconia powder, 20g of LD1132-50, 100g of anhydrous ethanol and 100g of butanone, and place them in a 2L ball mill. Adjust the roller mill speed to 70r / min and mill for 24h. ② Weigh 3000g of 10mm zirconia column, 1000g of 15mm zirconia column, 265g of anhydrous ethanol and butanone, and 120g of PVB and place them in a 5L ball mill. Adjust the roller mill speed to 70r / min and ball mill for 24h; ③ After the ball milling is completed, the slurry in the above 2L ball mill jar is filtered through an 80-mesh screen into the above 5L ball mill jar, and 900g of nano-alumina powder is added to continue ball milling for 7h; ④ After the ball milling is completed, the ball mill jar is removed and 72 g of DBP is added. The speed of the roller mill is adjusted to 30 r / min and the ball milling is continued for 17 h to obtain the green porcelain slurry.
[0034] This embodiment further provides a zirconium oxide composite alumina green ceramic, and the preparation method thereof comprises the following steps: ⑤ After the ball milling is completed, the slurry is filtered out and allowed to stand for 15 minutes, followed by a 20-minute degassing treatment; ⑥ The above slurry was cast into green porcelain at a speed of 0.5 m / min, and then cut, laminated, hot pressed, and cut into strip samples with a length of 40 mm, a width of 6 mm, and a thickness of 5 mm. After sintering, the flexural strength test was performed. The sample number was recorded as T3.
[0035] Example 4
[0036] This embodiment provides a green porcelain slurry, and the preparation method thereof comprises the following steps: ① Weigh 400g of 3mm zirconia balls, 500g of 5mm zirconia balls, 100g of titanate coupling agent modified nano-zirconia powder, 20g of LD1132-50, 100g of anhydrous ethanol and 100g of butanone, and place them in a 2L ball mill. Adjust the roller mill speed to 70r / min and mill for 24h. ② Weigh 3000g of 10mm zirconia column, 1000g of 15mm zirconia column, 265g of anhydrous ethanol and butanone, and 120g of PVB and place them in a 5L ball mill. Adjust the roller mill speed to 70r / min and ball mill for 24h; ③ After the ball milling is completed, the slurry in the above 2L ball mill jar is filtered through an 80-mesh screen into the above 5L ball mill jar, and 900g of nano-alumina powder is added to continue ball milling for 7h; ④ After the ball milling is completed, the ball mill jar is removed and 72 g of DBP is added. The speed of the roller mill is adjusted to 30 r / min and the ball milling is continued for 17 h to obtain the green porcelain slurry.
[0037] This embodiment further provides a zirconium oxide composite alumina green ceramic, and the preparation method thereof comprises the following steps: ⑤ After the ball milling is completed, the slurry is filtered out and allowed to stand for 15 minutes, followed by a 20-minute degassing treatment; ⑥ The above slurry was cast into green porcelain at a speed of 0.4m / min, and then cut, laminated, hot pressed, and cut into strip samples with a length of 40mm, a width of 6mm, and a thickness of 5mm. After sintering, the flexural strength test was performed. The sample number was recorded as T4.
[0038] Example 5
[0039] This embodiment provides a green porcelain slurry, and the preparation method thereof comprises the following steps: ① Weigh 400g of 3mm zirconia balls, 500g of 5mm zirconia balls, 100g of aluminate coupling agent-modified nano-zirconia powder, 20g of EW20000, 100g each of anhydrous ethanol and butanone, and place them in a 2L ball mill. Adjust the roller mill speed to 70r / min and mill for 24h; ② Weigh 3000g of 10mm zirconia column, 1000g of 15mm zirconia column, 265g of anhydrous ethanol and butanone, and 120g of PVB and place them in a 5L ball mill. Adjust the roller mill speed to 70r / min and ball mill for 24h; ③ After the ball milling is completed, the slurry in the above 2L ball mill jar is filtered through an 80-mesh screen into the above 5L ball mill jar, and 900g of nano-alumina powder is added to continue ball milling for 7h; ④ After the ball milling is completed, the ball mill jar is removed and 72 g of DBP is added. The speed of the roller mill is adjusted to 30 r / min and the ball milling is continued for 17 h to obtain the green porcelain slurry.
[0040] This embodiment further provides a zirconium oxide composite alumina green ceramic, and the preparation method thereof comprises the following steps: ⑤ After the ball milling is completed, the slurry is filtered out and allowed to stand for 15 minutes, followed by a 20-minute degassing treatment; ⑥ The above slurry was cast into green porcelain at a speed of 0.4m / min, and then cut, laminated, hot pressed, and cut into strip samples with a length of 40mm, a width of 6mm, and a thickness of 5mm. After sintering, the flexural strength test was performed. The sample number was recorded as T5.
[0041] Example 6
[0042] This embodiment provides a green porcelain slurry, and the preparation method thereof comprises the following steps: ① Weigh 400g of 3mm zirconia balls, 500g of 5mm zirconia balls, 100g of aluminate coupling agent modified nano-zirconia powder, 20g of LD1140, 100g of anhydrous ethanol and 100g of butanone, and place them in a 2L ball mill. Adjust the roller mill speed to 70r / min and mill for 24h; ② Weigh 3000g of 10mm zirconia column, 1000g of 15mm zirconia column, 265g of anhydrous ethanol and butanone, and 120g of PVB and place them in a 5L ball mill. Adjust the roller mill speed to 70r / min and ball mill for 24h; ③ After the ball milling is completed, the slurry in the above 2L ball mill jar is filtered through an 80-mesh screen into the above 5L ball mill jar, and 900g of nano-alumina powder is added to continue ball milling for 7h; ④ After the ball milling is completed, the ball mill jar is removed and 72 g of DBP is added. The speed of the roller mill is adjusted to 30 r / min and the ball milling is continued for 17 h to obtain the green porcelain slurry.
[0043] This embodiment further provides a zirconium oxide composite alumina green ceramic, and the preparation method thereof comprises the following steps: ⑤ After the ball milling is completed, the slurry is filtered out and allowed to stand for 15 minutes, followed by a 20-minute degassing treatment; ⑥ The above slurry was cast into green porcelain at a speed of 0.4m / min, and then cut, laminated, hot pressed, and cut into strip samples with a length of 40mm, a width of 6mm, and a thickness of 5mm. After sintering, the flexural strength test was performed. The sample number was recorded as T6.
[0044] Example 7
[0045] This embodiment provides a green porcelain slurry, and the preparation method thereof comprises the following steps: ① Weigh 900g of 10mm zirconia column, 100g of aluminate coupling agent modified nano-zirconia powder, 20g of LD1132-50, 100g of anhydrous ethanol and 100g of butanone, and place them in a 2L ball mill. Adjust the roller mill speed to 70r / min and mill for 24h; ② Weigh 4000g of 10mm zirconia column, 265g of anhydrous ethanol and butanone, and 120g of PVB into a 5L ball mill, adjust the roller mill speed to 70r / min and mill for 24h; ③ After the ball milling is completed, the slurry in the above 2L ball mill jar is filtered through an 80-mesh screen into the above 5L ball mill jar, and 900g of nano-alumina powder is added to continue ball milling for 7h; ④ After the ball milling is completed, the ball mill jar is removed and 72 g of DBP is added. The speed of the roller mill is adjusted to 30 r / min and the ball milling is continued for 17 h to obtain the green porcelain slurry.
[0046] This embodiment further provides a zirconium oxide composite alumina green ceramic, and the preparation method thereof comprises the following steps: ⑤ After the ball milling is completed, the slurry is filtered out and allowed to stand for 15 minutes, followed by a 20-minute degassing treatment; ⑥ The above slurry was cast into green porcelain at a speed of 0.4m / min, and then cut, laminated, hot pressed, and cut into strip samples with a length of 40mm, a width of 6mm, and a thickness of 5mm. After sintering, the flexural strength test was performed. The sample number was recorded as T7.
[0047] Comparative Example 1
[0048] This embodiment provides a green porcelain slurry, and the preparation method thereof comprises the following steps: ① Weigh 400g of 3mm zirconia balls, 500g of 5mm zirconia balls, 100g of nano zirconia powder, 20g of BYK22552, 100g of anhydrous ethanol and 100g of butanone, and place them in a 2L ball mill. Adjust the roller mill speed to 70r / min and mill for 24h. ② Weigh 3000g of 10mm zirconia column, 1000g of 15mm zirconia column, 265g of anhydrous ethanol and butanone, and 120g of PVB and place them in a 5L ball mill. Adjust the roller mill speed to 70r / min and ball mill for 24h; ③ After the ball milling is completed, the slurry in the above 2L ball mill jar is filtered through an 80-mesh screen into the above 5L ball mill jar, and 900g of nano-alumina powder is added to continue ball milling for 7h; ④ After the ball milling is completed, the ball mill jar is removed and 72 g of DBP is added. The speed of the roller mill is adjusted to 30 r / min and the ball milling is continued for 17 h to obtain the green porcelain slurry.
[0049] This embodiment further provides a zirconium oxide composite alumina green ceramic, and the preparation method thereof comprises the following steps: ⑤ After the ball milling is completed, the slurry is filtered out and allowed to stand for 15 minutes, followed by a 20-minute degassing treatment; ⑥ The above slurry was cast into green porcelain at a speed of 0.4m / min, and then cut, laminated, hot pressed, and cut into strip samples with a length of 40mm, a width of 6mm, and a thickness of 5mm. After sintering, the flexural strength test was performed. The sample number is recorded as A1.
[0050] Comparative Example 2
[0051] This embodiment provides a green porcelain slurry, and the preparation method thereof comprises the following steps: ① Weigh 3000g of 10mm zirconia column, 1000g of 15mm zirconia column, 100g of nano zirconia powder, and 900g of nano alumina powder and place them in a 5L ball mill; ② Add 365g of anhydrous ethanol and butanone, 20g of BYK22552, 120g of PVB, and 72g of DBP into the above ball mill; ② Place the ball mill on a roller mill and adjust the speed to 70 r / min for ball milling. After ball milling for 7 hours, adjust the speed to 30 r / min and continue ball milling for 17 hours to obtain the green porcelain slurry.
[0052] This embodiment further provides a zirconium oxide composite alumina green ceramic, and the preparation method thereof comprises the following steps: ③After the ball milling, filter out the slurry and let it stand for 15 minutes, followed by a 20-minute degassing treatment; ④ The above slurry was cast into green porcelain at a speed of 0.4m / min, and then cut, laminated, hot pressed, and cut into strip samples with a length of 40mm, a width of 6mm, and a thickness of 5mm. After sintering, the flexural strength test was performed. The sample number was recorded as A2.
[0053] Comparative Example 3
[0054] This embodiment provides a green porcelain slurry, and the preparation method thereof comprises the following steps: ① Weigh 3000g of 10mm zirconia column, 1000g of 15mm zirconia column, 365g of anhydrous ethanol and butanone, 20g of BYK22552, and 120g of PVB and place them in a 5L ball mill; ② Place the ball mill on the roller mill and adjust the speed to 70r / min for ball milling. After ball milling for 3h, remove the ball mill, add 100g of nano zirconium oxide powder and 900g of nano alumina powder, and continue ball milling for 4h; ③ After the ball milling is completed, the ball mill jar is removed and 72 g of DBP is added. The speed of the roller mill is adjusted to 30 r / min and the ball milling is continued for 17 h to obtain the green porcelain slurry.
[0055] This embodiment further provides a zirconium oxide composite alumina green ceramic, and the preparation method thereof comprises the following steps: ④After the ball milling is completed, the slurry is filtered out and allowed to stand for 15 minutes, followed by a 20-minute degassing treatment; ⑤ The above slurry was cast into green porcelain at a speed of 0.4m / min, and then cut, laminated, hot pressed, and cut into strip samples with a length of 40mm, a width of 6mm, and a thickness of 5mm. After sintering, the flexural strength test was performed. The sample number was recorded as A3.
[0056] Comparative Example 4
[0057] This embodiment provides a green porcelain slurry, and the preparation method thereof comprises the following steps: ① Weigh 400g of 3mm zirconia balls, 500g of 5mm zirconia balls, 100g of aluminate coupling agent-modified nano-zirconia powder, 20g of LD1132-50, 100g of anhydrous ethanol and 100g of butanone, and place them in a 2L ball mill. Adjust the roller mill speed to 70r / min and mill for 24h. ② Weigh 3000g of 10mm zirconia column, 1000g of 15mm zirconia column, 265g of anhydrous ethanol and butanone, and 120g of PVB and place them in a 5L ball mill. Adjust the roller mill speed to 70r / min and ball mill for 24h; ③ After the ball milling is completed, the slurry in the above 2L ball mill jar is filtered through an 80-mesh screen into the above 5L ball mill jar, and 900g of nano-alumina powder is added to continue ball milling for 7h; ④ After the ball milling is completed, the ball mill jar is removed and 72 g of DBP is added. The speed of the roller mill is adjusted to 30 r / min and the ball milling is continued for 17 h to obtain the green porcelain slurry.
[0058] This embodiment further provides a zirconium oxide composite alumina green ceramic, and the preparation method thereof comprises the following steps: ⑤ After the ball milling is completed, the slurry is filtered out and allowed to stand for 15 minutes, followed by a 20-minute degassing treatment; ⑥ The above slurry was cast into green porcelain at a speed of 0.3m / min, and then cut, laminated, hot pressed, and cut into strip samples with a length of 40mm, a width of 6mm, and a thickness of 5mm. After sintering, the flexural strength test was performed. The sample number was recorded as A4.
[0059] Comparative Example 5
[0060] This embodiment provides a green porcelain slurry, and the preparation method thereof comprises the following steps: ① Weigh 400g of 3mm zirconia balls, 500g of 5mm zirconia balls, 100g of aluminate coupling agent-modified nano-zirconia powder, 20g of LD1132-50, 100g of anhydrous ethanol and 100g of butanone, and place them in a 2L ball mill. Adjust the roller mill speed to 70r / min and mill for 24h. ② Weigh 3000g of 10mm zirconia column, 1000g of 15mm zirconia column, 265g of anhydrous ethanol and butanone, and 120g of PVB and place them in a 5L ball mill. Adjust the roller mill speed to 70r / min and ball mill for 24h; ③ After the ball milling is completed, the slurry in the above 2L ball mill jar is filtered through an 80-mesh screen into the above 5L ball mill jar, and 900g of nano-alumina powder is added to continue ball milling for 7h; ④ After the ball milling is completed, the ball mill jar is removed and 72 g of DBP is added. The speed of the roller mill is adjusted to 30 r / min and the ball milling is continued for 17 h to obtain the green porcelain slurry.
[0061] This embodiment further provides a zirconium oxide composite alumina green ceramic, and the preparation method thereof comprises the following steps: ⑤ After the ball milling is completed, the slurry is filtered out and allowed to stand for 15 minutes, followed by a 20-minute degassing treatment; ⑥ The above slurry was cast into green porcelain at a speed of 0.6 m / min, and then cut, laminated, hot pressed, and cut into strip samples with a length of 40 mm, a width of 6 mm, and a thickness of 5 mm. After sintering, the flexural strength test was performed. The sample number was recorded as A5.
[0062] Test example
[0063] The present invention further tests the flexural strength of the green porcelain of the above-mentioned embodiments and comparative examples, and the results are shown in Table 1.
[0064] Test method: GB / T 6569-2006
[0065] Table 1 Flexural strength of zirconia composite alumina substrate
[0066] It can be seen from Table 1 that the flexural strength of zirconium oxide composite alumina green porcelain can reach more than 600MPa. By comparing the experimental results of comparative example 1, embodiment 1 and embodiment 5, it can be seen that the zirconia composite alumina green porcelain prepared by modified zirconium oxide powder can greatly improve the flexural strength of the material. The modified zirconium oxide powder has strong organic affinity and lubricity, which promotes the dispersion degree of zirconium oxide powder. At the same time, the sintered product of the selected aluminate coupling agent can further improve the interface bonding degree between zirconium oxide and alumina, and the sintered product of the titanate coupling agent can promote the sintering of alumina powder. The experimental results of embodiment 1, embodiment 2, embodiment 5 and embodiment 6 can prove that the dispersant LD1132-50 has the best dispersing effect on zirconium oxide. The dispersant LD1132-50 is a modified styrene maleic acid polymer with a large variety of functional groups. Its non-polar benzene ring and hydrocarbon chain can be adsorbed on the non-polar surface of the particles, and the polar group or side chain covers the surface of the non-polar particles, generating electrostatic repulsion, thereby enhancing the degree of dispersion. Dispersant LD1140 is a block copolymer with a conjugated group. This dispersant will increase the viscosity of the slurry and affect the dispersibility of the powder. Dispersant EW20000 is a polymer dispersant with 100% active matter content. This dispersant easily causes the particle adsorption layer to penetrate each other, causing entropy increase, system free energy decrease, and particle agglomeration. Dispersant BYK22552 is a copolymer solution containing filler groups, in which -COOH allows it to be adsorbed on the surface of the particles to form a steric layer, producing a steric effect, but the single functional group has a poor powder dispersion effect, resulting in a large degree of discreteness in material strength. The same conclusion can be obtained through SEM images. The experimental results of Example 3, Example 4 and Comparative Example 4 and Comparative Example 5 prove that too fast or too slow flow rate will lead to a decrease in flexural strength. The experimental results of Example 2 and Example 7 prove that the use of small-particle grinding balls with different particle sizes has a significant promoting effect on powder dispersion, and the use of large-particle grinding columns with different particle sizes can ensure that the slurry is fully mixed and improve the material strength.
[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a raw porcelain slurry, characterized in that: include: S1: mixing a first dispersant, a coupling agent, zirconium oxide powder and a first organic solvent, and obtaining modified zirconium oxide powder after ball milling and drying; S2: mixing the modified zirconium oxide powder, aluminum oxide powder, a second dispersant and a second organic solvent, and preparing a first slurry by ball milling; S3: mixing the first slurry with the binder solution and continuing ball milling, adding a plasticizer after the ball milling and continuing ball milling to obtain the green porcelain slurry.
2. The method for preparing a green porcelain slurry according to claim 1, characterized in that: The coupling agent includes an aluminate coupling agent and / or a titanate coupling agent; preferably, the added amount of the coupling agent is 1wt% to 3wt% of the mass of the zirconium oxide powder.
3. The method for preparing a green porcelain slurry according to claim 1, characterized in that: The first dispersant and the second dispersant each independently, identically or differently include one or more of EW20000, BYK22552, LD1140 and LD1132-50; preferably, the first dispersant and the second dispersant each independently, identically or differently include BYK22552 and / or LD1132-50; More preferably, the added amount of the first dispersant is 0.5wt%~2.5wt% of the mass of the zirconium oxide powder; the added amount of the second dispersant is 0.5wt%~2.5wt% of the total mass of the modified zirconium oxide powder and the alumina powder.
4. The method for preparing the green porcelain slurry according to any one of claims 1 to 3, characterized in that: The zirconium oxide powder is a nano monoclinic zirconium oxide powder, and D50 is 400-600nm; and / or, the alumina powder is a nano alumina powder, and D50 is 400-600nm; Preferably, the mass of the modified zirconium oxide powder is 8wt% to 15wt% of the mass of the aluminum oxide powder.
5. The method for preparing the green porcelain slurry according to any one of claims 1 to 4, characterized in that: The first ball milling medium is added during the mixing in S1, and the second ball milling medium is added during the mixing in S2; wherein the particle size of the first ball milling medium is 1-5 mm, and the particle size of the second ball milling medium is 10-15 mm.
6. The method for preparing the green porcelain slurry according to any one of claims 1 to 5, characterized in that: The binder solution includes a binder and an organic solvent, the binder includes one of PVB and / or PMMA, and the organic solvent includes one or more of acetone, butanone, ethyl acetate and butyl acetate; preferably, the addition amount of the binder is 8wt%~12wt% of the total mass of the modified zirconium oxide powder and the alumina powder.
7. The method for preparing a green porcelain slurry according to any one of claims 1 to 6, characterized in that: The plasticizer is one or more of dibutyl phthalate and dioctyl phthalate.
8. A raw porcelain slurry, characterized in that: The raw porcelain slurry is prepared by the method for preparing the raw porcelain slurry according to any one of claims 1 to 7.
9. A method for preparing zirconium oxide composite alumina raw porcelain, characterized in that: include: The green porcelain slurry according to claim 8 is allowed to stand for degassing, and then cast to obtain zirconium oxide composite alumina green porcelain, wherein the casting speed is 0.4-0.5 m / min.
10. A zirconium oxide composite alumina green porcelain, characterized in that: The zirconium oxide composite alumina raw ceramic is prepared by the preparation method of claim 9.
Citation Information
Patent Citations
Preparation method of zirconium oxide ceramic for oxygen sensor
CN104891969A
Method for preparing zirconia ceramic piece through in-situ curtain coating
CN107399969A
Zirconia-doped alumina ceramic and preparation method thereof
CN112939582A
Zirconium oxide toughened aluminum oxide ceramic plate and preparation method thereof
CN113292323A
Modified wollastonite as well as preparation method and application thereof
CN114410130A
Cited By
Insulating high-fracture-resistance aluminum oxide multilayer ceramic substrate and preparation method thereof
CN120887711A
Highly insulating, high flexural strength alumina multilayer ceramic substrate and method of making same
CN120887711B